Specimens other than bone are not acceptable for microbiological diagnosis of chronic osteomyelitis. Prospective study with 100 patients (2003)
ABSTRACT: Background: Chronic osteomyelitis (COM) is very difficult to cure without proper identification of the bone-infecting organism and it is not clear whether specimens other than bone are appropriate for microbiological diagnosis because results from available studies are conflicting. Methods: Prospective analysis of 100 patients with COM in a 500-bed University-based hospital, comparing the microbiology from specimens other than bone with that of bone cultures, taking the last as the gold standard. Results: Time of evolution of COM was 1 to 384 days (median 180 days), 72% of patients were male, mean age was 38±18 years. Femur and tibia accounted for 72% of the infected bones; most had trauma and/or surgery (85%) as predisposing factors. The microbiology of speci- mens other than bone was identical to that found after simultaneous bone cultures in 30%; concordance for Staphylococcus aureus was 41% and for other microorganisms 18%. These concordance rates correspond to 74% sensibility, 6% specificity, 30% positive predictive value, and 31% negative predictive value. Anaerobic bacteria were isolated from the bone in 13% of patients. Conclusions: Diagnosis and therapy of chronic osteomyelitis cannot be guided by cultures of non-bone specimens because their microbiology is substantially different to the microbiology of the infected bone.